(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Evaluation of groundwater resources of Girei and environs is necessary in order to develop appropriate water supply scheme to the community. Cases of borehole failures have been on increase in the area due to a lack of knowledge of the aquifer geometry. The study is aimed at delineating the groundwater potential zones of Girei and environs with the objectives of delineating the different aquifer systems, estimating the aquifer characteristics such as transmissivity and hydraulic conductivity using the Dar Zarrouk parameter, determining groundwater flow direction, and identifying the recharged and discharged areas. Geological investigation indicates that the area underlain by Bima sandstone. Thirty profiles of Vertical Electrical Sounding using Schlunberger array method with the aid of ABEM signal averaging system (SAS 1000) was used to determine aquifer types and groundwater potential zones. Correlation between borehole lithological section and geoelectric section within the study area revealed a confineded aquifer type. The aquifer characteristics indicate that the transverse resistance ranged between 29.796 to 238000 ?m2, longitudinal conductance ranged between 0.0148 ?-1 to 9.34 ?-1, hydraulic conductivity values range from 0.0014 to 5.865 m/s with an average value of 0.0355 m/s. Transmissivity values obtained from the various layers range from 237.6 m2/day to 6324 m2/day. Aquifer rating based on transmissivity values reveals that the aquifers in the study area have moderate to high potential.